Entrepreneurship in the Periphery and the Role of Social Networks: A Study of Businesses in Iqaluit, Nunavut - McCluskey, Christopher J (University of Ottawa (Canada), 2011)
The notion of Canada as a cultural mosaic is especially vivid when comparing life in Nunavut to that of the rest of the country. Not only is the predominant Inuit culture unique in many ways, but so too are the geographical characteristics that make Nunavut and the Canadian North so different from many other regions in the country. To gain a better understanding of entrepreneurship in Nunavut, the research explores how entrepreneurs build and use their social networks and the role of brokerage and closure in the entrepreneurial process. Using a qualitative approach of observation and interviews in the field to gather the data, the findings describe how networks are used in business in the North, and support the conclusion that networks are important for the coordination of resources.